Empagliflozin increases kidney weight due to increased cell size in the proximal tubule S3 segment and the collecting duct - Sinha, Frederick; Federlein, Anna; Biesold, Annika; Schwarzfischer, Magdalena; Krieger, Katharina; Schweda, Frank; Tauber, Philipp (Frontiers in Pharmacology, 2023)
The inhibition of renal SGLT2 glucose reabsorption has proven its therapeutic efficacy in chronic kidney disease. SGLT2 inhibitors (SGLTi) have been intensively studied in rodent models to identify the mechanisms of SGLT2i-mediated nephroprotection. So far, the overwhelming effects from clinical trials, could only partially be reproduced in rodent models of renal injury. However, a commonly disregarded observation from these studies, is the increase in kidney weight after SGLT2i administration. Increased kidney mass often relies on tubular growth in response to reabsorption overload during glomerular hyperfiltration. Since SGLT2i suppress hyperfiltration but concomitantly increase renal weight, it seems likely that SGLT2i have a growth promoting effect on the kidney itself, independent of GFR control. This study aimed to investigate the effect of SGLT2i on kidney growth in wildtype animals, to identify enlarged nephron segments and classify the size increase as hypertrophic/hyperplastic growth or cell swelling. SGLT2i empagliflozin increased kidney weight in wildtype mice by 13% compared to controls, while bodyweight and other organs were not affected. The enlarged nephron segments were identified as SGLT2-negative distal segments of proximal tubules and as collecting ducts by histological quantification of tubular cell area. In both segments protein/DNA ratio, a marker for hypertrophic growth, was increased by 6% and 12% respectively, while tubular nuclei number (hyperplasia) was unchanged by empagliflozin. SGLT2-inhibition in early proximal tubules induces a shift of NaCl resorption along the nephron causing compensatory NaCl and H2O reabsorption and presumably cell growth in downstream segments. Consistently, in collecting ducts of empagliflozin-treated mice, mRNA expression of the Na+-channel ENaC and the H2O-channels Aqp-2/Aqp-3 were increased. In addition, the hypoxia marker Hif1α was found increased in intercalated cells of the collecting duct together with evidence for increased proton secretion, as indicated by upregulation of carbonic anhydrases and acidified urine pH in empagliflozin-treated animals. In summary, these data show that SGLT2i induce cell enlargement by hypertrophic growth and possibly cell swelling in healthy kidneys, probably as a result of compensatory glucose, NaCl and H2O hyperreabsorption of SGLT2-negative segments. Particularly affected are the SGLT2-negative proximal tubules (S3) and the collecting duct, areas of low O2 availability.